Optimizing the growth conditions of superconducting MoSi thin films for single photon detection - Stefanie Grotowski; Lucio Zugliani; Björn Jonas; Rasmus Flaschmann; Christian Schmid; Stefan Strohauer; Fabian Wietschorke; Niklas Bruckmoser; Manuel Müller; Matthias Althammer; Rudolf Gross; Kai Müller; et al. (Scientific Reports)
Abstract We investigate the growth of amorphous MoSi thin films using magnetron co-sputtering and optimize the growth conditions with respect to crystal structure and superconducting properties (e.g., critical temperature $$T_{\text {c}}$$ ). The deposition pressure, Mo:Si stoichiometry and substrate temperature are systematically varied to achieve a transition temperature of 8.4(3) K for films with a thickness of 17.7(8) nm and 6.2(9) K for a 4.3(4) nm thick film. For Mo concentrations above 81% the crystalline phase $$\hbox {Mo}_\text {3}$$ Mo 3 Si is observed in grazing incidence X-ray diffraction measurements. The same phase appears when the working pressure during deposition is reduced below 3. $$1 × 10^{\text {-3}}\hspace{1.66656pt}$$ 1 × 10 -3 mbar and when the substrate temperature during deposition is increased above $$100\hspace{1.66656pt}^{° } $$ C. By choosing a sufficient Si concentration and optimum deposition pressure we identify deposition conditions that ensure a homogeneous amorphous growth of the superconducting thin film. We then fabricate superconducting nanowire single-photon detectors which exhibit an unitary internal efficiency to single photons at an operational temperature of 1.2 K while simultaneously having a dark count rate below 1 Hz. Our results establish the link between MoSi film deposition, morphology and the performance of SSPD.